IMPLEMENTASI PENDAMPINGAN PROMOSI DESA WISATA PENTINGSARI MELALUI MEDIA SOSIAL - Zaki, Ahmad; Chantika, Shakira Ratu (Dharma: Jurnal Pengabdian Masyarakat, 2024)
Pentingsari Tourism Village is one of the tourist villages in Pentingsari, Umbulharjo, Cangkringan, Sleman Regency, Yogyakarta Special Region. Pentingsari Tourism Village has various tourist attractions that target domestic and foreign tourists. However, this tourist village still uses marketing media that has not been digitized. Pentingsari Tourism Village has not maximized the use of social media as a marketing medium in an effort to attract tourists. This community service is carried out through a direct visitation stage followed by the implementation of social media as a promotional tool for Pentingsari Tourism Village. The results obtained, namely the promotional content of Pentingsari Tourism Village, received positive and negative evaluations. Advertisers have applied the AIDA concept to content production, but still lack engagement. In addition, when promotions get a poor response, advertisers need to optimize the marketing funnel in order to increase brand image and engagement rate on the products or services offered.